The Summer Surface Energy Budget of the Ice-Free Area of Northern James Ross Island and Its Impact on the Ground Thermal Regime - Klára Ambrožová; Filip Hrbáček; Kamil Láska (Atmosphere, 2020)
Despite the key role of the surface energy budget in the global climate system, such investigations are rare in Antarctica. In this study, the surface energy budget measurements from the largest ice-free area on northern James Ross Island, in Antarctica, were obtained. The components of net radiation were measured by a net radiometer, while sensible heat flux was measured by a sonic anemometer and ground heat flux by heat flux plates. The surface energy budget was compared with the rest of the Antarctic Peninsula Region and selected places in the Arctic and the impact of surface energy budget components on the ground thermal regime was examined. Mean net radiation on James Ross Island during January–March 2018 reached 102.5 W m−2. The main surface energy budget component was the latent heat flux, while the sensible heat flux values were only 0.4 W m−2 lower. Mean ground heat flux was only 0.4 Wm-2, however, it was negative in 47% of January–March 2018, while it was positive in the rest of the time. The ground thermal regime was affected by surface energy budget components to a depth of 50 cm. The strongest relationship was found between ground heat flux and ground surface temperature. Further analysis confirmed that active layer refroze after a sequence of three days with negative ground heat flux even in summer months. Daily mean net radiation and ground heat flux were significantly reduced when cloud amount increased, while the influence of snow cover on ground surface temperature was negligible.